Left Ventricular Remodeling Shortly after Open Mitral Valve Replacement for Rheumatic Mitral Stenosis - Marcus Vinicius Silva Ferreira (Brazilian Journal of Cardiovascular Surgery, 2021)
Abstract Introduction: Left ventricular dysfunction after surgical treatment of mitral stenosis is uncommon. We intend to determine the pattern of left ventricular remodeling, shortly after open mitral valve replacement for rheumatic mitral stenosis, with in-hospital postoperative outcomes and the determinants of postoperative worsening of left ventricular ejection fraction. Methods: From January 2008 to January 2015, 107 adult patients with rheumatic mitral stenosis were submitted to open mitral valve replacement. Their mean age was 45±11 years and 93 (86.9%) were women. Left ventricular morphology and function were studied longitudinally with echocardiography. The end point was postoperative worsening of left ventricular ejection fraction, defined by a decrease of 10% compared to preoperative basal assessment. Determinants of worsening left ventricular ejection fraction were determined by multivariable logistic regression analysis. Results: The end point occurred in 18 patients (16.8%). We tested clinical and echocardiographic parameters to verify independent variables related to the decrease in postoperative ejection fraction. Lower body weight (P=0.005; odds ratio [OR]=0.89) and smaller preoperative mitral valve area (P=0.02; OR=0.02) were independent predictors of left ventricular dysfunction. These patients presented higher mortality and morbidity rates. Conclusion: Left ventricular remodeling patterns differed among patients with predominant rheumatic mitral stenosis undergoing open mitral valve replacement. Lower preoperative body weight and mitral valve area were independent determinants of deteriorating ejection fraction with increased end-systolic volumes, indicating that this specific problem may occur in anthropometric smaller patients with more extensive rheumatic disease.